Crianças e infâncias: um olhar de azul para os trabalhos apresentados no GT07 da ANPED - Santos, Tatiani Rabelo Lapa (2014)
This research aims to investigate the production about the issues related to the Play, to toys, to plays and to toy library presented in the papers published in the period of 1988-2010, in the Working Group \"Education of children 0 to 6 years\" (GT07) of the Annual Meetings in National Association of Post-Graduation and Research in Education (ANPEd). Therefore, we used as methodology the bibliographic research and the documentary research with content analysis. In the first instance, we presented how the theoretical conceptions concerning children and childhoods were historically constituted and pointed the authors who discuss issues related to the Play, to plays, to toys and toy libraries. Posteriorly, guided by theoretical studies of Sociology of Childhood, we seek to understand what the authors/researchers, who participated in the GT07, write about children and childhood; which are the national and foreign production that composes the papers presented; which is the place of the childhood culture in this production and how these authors address issues related to the Play, to plays, to toys and toy libraries. After the full reading and analysis of the selected texts - 62 papers - it was verified that is common among such investigators, according to papers presented at the GT07, value children as beings capable of speaking in his own right, to give information and opinions about its educational, social and cultural world. The Play and the plays appear in the texts such as children\'s rights and possibility to interact with the world that around them. The analyzed papers shown that the authors, by observing the schools, report the predominance of the disciplinary role and the schooling activities proposed by education professionals and the Play and the plays treated as activities to \"discharge the energy\"; the researches presented in GT07 considers that many professionals treats the Play as something not serious; concomitantly, shows that even in front of a disciplinary and authoritarian context, children play, interact and create different resistance mechanisms for the established in the school routine and alter the prohibitions for the play, not restricted to what is imposed by teachers , inventing games and different forms playing. In this direction, we believe that the appreciation of children and childhoods found in the references used and in the works of the GT07 should be shared and reflected by all professionals that work with these subjects, at different educational spaces, so we can, in fact, produce different results, more human and humanizing in the schools.